The Ohdo blepharophimosis syndrome: a third case. - Biesecker, L G (1991)
A patient with a syndrome consisting of blepharophimosis, simple ears, hypoplastic teeth, developmental delay, and hypotonia is described. Previous case reports are reviewed and a differential diagnosis is described. Many of the features in the subject are similar to those described in two previous reports and they constitute a distinct syndrome.